Internal control in the autonomy mechanism: A study at Vietnamese public universities - Pham, Thi Thu Trang; Nguyen, Thi Thanh Hoa; Pham, Thu Huyen; Dao, Thi Nhung (Edelweiss Applied Science and Technology, 2026)
This study investigates the interaction between internal control (IC) and the autonomy mechanism and its impact on the operational performance of Vietnamese public universities. The paper is based on Agency theory, Contingency theory, and previous studies to build the research model. A questionnaire was developed, distributed, and collected from leaders, officials, lecturers, and staff of Vietnamese public universities, selected using random sampling. Quantitative analysis methods employed include Cronbach’s Alpha, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM). The research results indicate that the autonomy mechanism enhances the influence of internal control on organizational performance. However, unlike previous studies, the findings suggest that managerial autonomy has a minor negative impact on the performance of public universities. Based on the results, the paper proposes instructive recommendations for governmental agencies and universities in setting internal controls to improve performance within the context of the autonomy mechanism.